The Market Power of Brazilian Private Higher Education Institutions: An Efficiency-Frontier Approac - Ana Maria de Paula Morais; Silvinha Vasconcelos; Marcelo Resende (CESifo GmbH, 2024)
The Brazilian government started to implement, mainly from the 2000s onwards, mechanisms to stimulate the supply and demand for higher education in Brazil. Especially the offer of private higher education has shown strong growth in recent years as a result of systematic public policies, which has increased competition in this market. In this expansion scenario, it remains to be seen how the competitive market environment is configured in terms of market power. Therefore, this article intends to estimate the market power of Brazilian higher education institutions - HEIs from an alternative use of the stochastic frontier model, as proposed by Kumbhakar et. al (2012), for the period 2010 to 2019. This method is adopted because it solves the impasse of the lack of information on marginal costs, which prevents the application of other models for estimating market power. The results pointed to the presence of positive and significant market power of Brazilian HEIs, which may imply anti-competitive behavior.
Keywords: I22; L10; 330; higher education market; market power; stochastic frontier